Morphological study and performance deterioration of sustainable lignocellulosic corn fiber biocomposites - AL-Oqla, Faris M.; Sapuan, S.M. (Springer, 2022)
Continuous efforts are paid to facilitate finding sustainable ecofriendly functional alternative materials for green products form low-cost renewable lignocellulosic materials. In this work, several structural and treatment parameters were considered to investigate their effects on achieving sustainable low-cost biomaterials with desirable mechanical properties for the sustainable green products. Mediterranean corn agro waste lignocellulosic fibers were utilized in preparing bio-composite materials with polypropylene polymers before and after chemical treatments. Low-cost treatment solutions as sodium chloride, phosphoric acid (H3PO4), and citric acid (C6H8O7) solution were considered to investigate their effects on the mechanical performance enhancement and deterioration of the produced bio-composites. Various composites were designed with different reinforcement conditions, chemical treatments as well as untreated fibers, and were investigated regarding integrated mechanical performance criteria. Results have revealed that the produced composites were capable of enhancing the tensile strength to reach about 87 MPa with the untreated paper corn fibers comparable to the 38 MPa of the matrix alone. The effects of acids as well as sodium chloride treatments demonstrate that the modulus of elasticity of the composites decreased with increasing fiber contents. It was demonstrated that the modulus of elasticity was 5.87 GPa due to acids at 20wt. % fiber content, while that for the same fiber content due to sodium chloride was 6.88 GPa. The morphological characteristics of the prepared composites were investigated using a scanning electron microscope (SEM) to support their performance assessment and results gained. It was also noticed that the combination and synergy between the considered various parameters on several mechanical properties of the bio-composites would enhance evaluating such materials from technical stand point, and demonstrate their suitability for future sustainable cleaner production.